2021
DOI: 10.1093/gbe/evab196
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of Purifying Selection on SARS-CoV-2

Abstract: Owing to a lag between a deleterious mutation’s appearance and its selective removal, gold-standard methods for mutation rate estimation assume no meaningful loss of mutations between parents and offspring. Indeed, from analysis of closely related lineages, in SARS-CoV-2 the Ka/Ks ratio was previously estimated as 1.008, suggesting no within-host selection. By contrast, we find a higher number of observed SNPs at 4-fold degenerate sites than elsewhere and, allowing for the virus’s complex mutational and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 69 publications
2
41
0
Order By: Relevance
“…The analysis of the diffusion of specific missense mutations in the human population has received particular attention throughout the pandemic evolution 3 , 8 , 9 , 12 22 . It has been pointed out that the D614G mutation, a non-conservative mutation with a PAM value of 11, in the Spike protein, which occurred through a single base change, has increased the virus infectivity 23 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the diffusion of specific missense mutations in the human population has received particular attention throughout the pandemic evolution 3 , 8 , 9 , 12 22 . It has been pointed out that the D614G mutation, a non-conservative mutation with a PAM value of 11, in the Spike protein, which occurred through a single base change, has increased the virus infectivity 23 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the genetic diversity of SARS-CoV-2, a study evaluating hospitalized patients in China in early 2020 found a mutation rate of 1.1-6.2 × 10 −3 /site/year [37]. More recent studies suggest a lower mutation rate, between 1.5-1.7 × 10 −3 /site/year [38]. This rate is similar than other RNA viruses such as seasonal influenza (H1N1, H3N2) with a rate between 0.6-2.0 × 10 −3 /site/year [37].…”
Section: Relevant Characteristics Of the Sars-cov-2 Genomementioning
confidence: 99%
“…Mutation statistics by the National Genomics Data Center ( https://ngdc.cncb.ac.cn/ ) and other reports showed that the rate of viral mutation of the spike protein has continued to increase since the SARS‐CoV‐2 pandemic 13 and new variants continue to emerge. Based on this, the World Health Organization (WHO) classifies variants into variants of concern (VOCs) and variants of interest (VOI) based on the degree of variability in transmissibility, virulence, or diagnostic/therapeutic/vaccine efficacy.…”
Section: Introductionmentioning
confidence: 99%